Between Realism and Reflexivity: Interrogating Theatrical Form in Bruised Evenings and Journey with the Body of Tim - Khadka , Dharmaraj; Shrestha, Rajan (Bodhi: An Interdisciplinary Journal, 2025)
This article explores the interplay between realism and reflexivity in two of Abhi Subedi’s plays, Bruised Evenings and Journey with the Body of Time. The study, through a metatheatrical reading, investigates how Subedi deviates from traditional theatrical forms. It also analyzes embedding self-referential devices, symbolic layering, character fragmentation, and ruptures within realist narrative structures. Drawing on Richard Hornby’s taxonomy of metadrama and critical perspectives from Lionel Abel, Patrice Pavis, and Ching-jung Chiu, the article analyzes how these plays engage in a dynamic dialogue with theatre itself to transform performance into both form and content. Despite being based on socio-political and cultural concerns, Subedi’s dramaturgy transcends conventional narrative boundaries and fuses ritual, myth, memory, and performativity in reflexive style. The paper concludes that Subedi’s strategic use of metatheatre rejects realism and at the same time creatively redefines it. Such use of technique also opens up new aesthetic and philosophical possibilities for Nepali theatre. This study is also expected to contribute to a broader understanding of theatrical innovation in South Asian drama and invites further scholarly engagement with Nepali plays as fertile area of artistic experimentation and expression.